2006
DOI: 10.1007/bf03344157
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of radioiodine (131-I) as definitive therapy in patients with autoimmune and non-autoimmune hyperthyroidism

Abstract: We evaluated the outcome of radioiodine (RAI) therapy in 100 consecutive patients treated in the period 2000-2001 for hyperthyroidism due to Graves' disease (GD), toxic adenoma (TA) and toxic multinodular goiter (TMG). Thyroid function was measured before and after therapy every 3-6 months up to 3 yr. Three years after therapy, 75% of TA patients were euthyroid, 18.7% were hypothyroid and 6.3% hyperthyroid. Of the TMG patients, 62.2% were euthyroid, 18.9% were hypothyroid and 18.9% hyperthyroid. In GD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 13 publications
3
15
0
4
Order By: Relevance
“…This is in keeping with previous studies which have reported success of RIA therapy to be over 85% [41, 42]. …”
Section: Discussionsupporting
confidence: 92%
“…This is in keeping with previous studies which have reported success of RIA therapy to be over 85% [41, 42]. …”
Section: Discussionsupporting
confidence: 92%
“…Altogether, these results, both in terms of effectiveness with a single administration (main endpoint) and in terms of minimizing the risk of hypothyroidism (secondary endpoint), are fair, when compared with those reported in literature [3][4][5] In one long-term follow-up study on patients treated with radioiodine, a prevalence of hypothyroidism of 3 % at 1 year and 64 % at 24 years was shown [19]. It is likely that the administration of lower activities with respect to other dosimetric methods can also offer advantages in terms of reduction of the long-term hypothyroidism incidence.…”
Section: Discussionsupporting
confidence: 60%
“…Radioiodine therapy with 131 I-iodide is one of the treatments of choice of MTG, together with surgery [3][4][5]. In fact, antithyroid drugs, as a rule, are unable to achieve hyperthyroidism cure.…”
Section: Introductionmentioning
confidence: 99%
“…Tarantini [27] found that with a median activity of 555 MBq, 75% of patients with toxic adenoma were euthyroid and 18.7% were hypothyroid, 3 years after iodine therapy. As expected, on decreasing the dose, the rate of hypothyroidism seems to be decreasing as well.…”
Section: Discussionmentioning
confidence: 99%